Peran Etika dan Keteladanan Guru dalam Pembentukan Karakter Anak Usia Dini di TK Aisyiyah ABA 10 - Aman Simaremare; Michael Yudha Pratama; Regina Melviani Br Sebayang; Roito Elya Lumban Batu; Arin Meira Sembiring; Latifa Arminati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Early childhood education is an important stage in shaping children's character and personality. In this process, teachers play a role not only as educators but also as role models in shaping students’ attitudes and behavior. This study aims to determine how teacher ethics and character contribute to the character building of early childhood students at TK Aisyiyah ABA 10. The research used a qualitative method with a case study approach. Data collection techniques were carried out through direct interviews with teachers at the school. The results of the study showed that character building in children is implemented through habituation, role modeling, good communication, and cooperation between teachers and parents. The character values instilled include discipline, honesty, responsibility, politeness, and religious attitudes. The findings indicate that teachers’ ethics and character have a very important influence on the character development of early childhood children.